Therapy with murinized tobevibart and elebsiran is efficacious in a liver-chimeric mouse model of HDV infection - Jiayi Zhou; Hannah Kaiser; Evelyn Rocha; Ashley N. Terrell; Davide Corti; Lisa A. Purcell; Florian A. Lempp; Andreas S. Puschnik (JHEP Reports)
Background & Aims: Chronic hepatitis delta virus (HDV) infection represents the most severe form of viral hepatitis. HDV is a satellite virus of hepatitis B virus (HBV) and depends on the hepatitis B surface antigen (HBsAg) for envelopment and viral entry. Tobevibart (VIR-3434) is an investigational monoclonal antibody targeting the antigenic loop of HBsAg. Elebsiran (VIR-2218) is an investigational RNAi therapeutic targeting a highly conserved region within the HBV genome. The aim of this study was to investigate the antiviral effect of tobevibart and elebsiran on HDV infection in preclinical models. Methods: In vitro antiviral activity was determined in an HBV/HDV coinfection model in primary human hepatocytes (PHHs) or Huh7-NTCP cells. The in vivo efficacy of a murinized version of tobevibart alone or in combination with elebsiran was evaluated in HBV/HDV-coinfected liver-chimeric mice. Results: Elebsiran treatment reduced levels of secreted HBsAg and infectious HDV with picomolar potency. Tobevibart exhibited pan-genotypic neutralizing activity against all tested HDV genotypes with EC50 ranging from 1.1 to 4.6 ng/ml. Combination treatment with tobevibart and elebsiran reduced infectious HDV levels in HBV/HDV-coinfected PHHs in an additive manner. In vivo, compared to vehicle, treatment with elebsiran, murinized tobevibart, or their combination significantly decreased HDV RNA serum levels by 0.7 log (p <0.0001), 1.6 log (p = 0.0034) and 2.1 log (p = 0.0002), respectively (measured at day 14 for elebsiran or day 21 for murinized tobevibart and the combination). HBsAg serum levels were reduced by 0.6 log (p <0.0001), 2.0 log (p <0.0001) and 2.8 log (p <0.0001), respectively. Conclusions: Tobevibart and elebsiran exert potent antiviral activity as single agents and in combination. The data support the clinical development of tobevibart and elebsiran for the treatment of patients with chronic HDV infection. Impact and implications: Chronic hepatitis delta is the most severe form of viral hepatitis and is associated with rapid progression of liver-related diseases and a high risk of hepatocellular carcinoma development. To date, there are only limited treatment options available. Tobevibart and elebsiran are currently being evaluated in clinical trials for the treatment of HDV (phase III) and for the treatment of HBV (phase II). The current study demonstrates that tobevibart and elebsiran are efficacious in preclinical models of HBV/HDV coinfection, supporting their clinical development.